2021
DOI: 10.1126/scisignal.aaw4673
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing cysteine oxidation sites by high-resolution proteomics reveals a mechanism of redox-dependent inhibition of human STING

Abstract: Protein function is regulated by posttranslational modifications (PTMs), among which reversible oxidation of cysteine residues has emerged as a key regulatory mechanism of cellular responses. Given the redox regulation of virus-host interactions, the identification of oxidized cysteine sites in cells is essential to understand the underlying mechanisms involved. Here, we present a proteome-wide identification of reversibly oxidized cysteine sites in oxidant-treated cells using a maleimide-based bioswitch metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 133 publications
2
24
0
Order By: Relevance
“…These results support the reduced ability of these genes to polymerize, dimerize or phosphorylate after overexpression to elicit downstream IFN signaling, as has been previously reported with wild-type STING expression in the absence of ligand. 53 Collectively, these studies suggested that MAVS expression in CRCs was capable of eliciting innate immune signaling, but had a more marginal effect in stimulating apoptosis and directly suppressing cellular proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…These results support the reduced ability of these genes to polymerize, dimerize or phosphorylate after overexpression to elicit downstream IFN signaling, as has been previously reported with wild-type STING expression in the absence of ligand. 53 Collectively, these studies suggested that MAVS expression in CRCs was capable of eliciting innate immune signaling, but had a more marginal effect in stimulating apoptosis and directly suppressing cellular proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress induces the intermolecular disulfide bond formation of TFEB/TFE3 in mammals, which enhances the activity of the TF 1370 . STING is a key regulator in the innate immune type I IFN pathway, and its C206 oxidation to form intermolecular disulfide bonds leads to a conformational change in the protein that prevents excessive activation of STING 1371 . In addition, cellular structure is also dependent on cysteine disulfides, as microtubule assembly is partly mediated by disulfide bonds 1345 …”
Section: Redox Modificationsmentioning
confidence: 99%
“…Another recent study by Cuervo et al. reported the Cys sites for redox‐dependent inhibition of human STING [118], which is known for its role as a central adaptor of the interferon (IFN) pathway in innate immune defense when the system detects DNA from pathogen. In this study, a maleimide‐based BST approach coupled with MS was applied to identify ∼2700 Cys sites, and reversible oxidation of Cys148 and Cys206 in STING was observed.…”
Section: Highlighted Applications Of Redox Proteomicsmentioning
confidence: 99%